The Russo-Georgian war and beyond: towards a European great power concert - Henrik Boesen Lindbo Larsen (Danish Institute for International Studies (DIIS), 2010)
This paper takes an in-depth look at the European great powers France, Germany and Britain and their foreign policy reactions vis-à-vis the Russo-Georgian War in August 2008. It explains the different reactions from a certain interplay between present and past geopolitics that shape the foreign policy choice of each state. France exhibited an 'overwhelming' identification with her EU presidency role reflected in France's balancing principles and multipolar ambitions with the EU acting as major global actor.Germany's 'overcautious' reactions to Russia are explained by Germany's self-imposed restraint in foreign affairs and identification with Russia as 'cornered' great power (analogy to Germany's defeat in WW1). Britain's hawkish reactions towards Russia reflect fundamental balancing principles that are simultaneously influenced by Britain's self-defined 'special relationship' with the USA. The paper points at a possible emerging great power concert, also beyond the Russo-Georgian War. While real foreign policy divergences at the purely rhetoric level crystallised during the immediate crisis, pragmatism and an interest-based approach towards Russia took over in the longer term. Here, great powers consensuses serve as main axes for alignment: while France and Germany remains the stable element, backing from Britain is essential to ensure band-wagoning among the Atlanticist-oriented states, notably the former communist states in Eastern Europe.
Keywords: 330; Internationale Beziehungen; Außenpolitik; Deutschland; Frankreich; Großbritannien; EU-Staaten; Russland